Lesbian, gay, bisexual, trans and queer psychology: an introduction - Clarke, Victoria (Cambridge Univ. Press, 2010)
"This textbook introduces students to the psychology of lesbian, gay, bisexual, trans and queer lives and experiences. It covers a broad range of topics including diversity, prejudice, health, relationships, parenting and lifespan experiences from youth to old age."--Jacket